Effect of Maspin Gene Methylation Induced by Specific shRNA Sequences on the Proliferation of Oral Squamous Cell Carcinoma HN13 Cells: Effect of Maspin Gene Methylation on Proliferation of OSCC Cells - Wu, Jingwen; Liu, Yi; Wang, Wenjing; Wang, Haichao; Zhang, Hongyi (Cellular and Molecular Biology, 2023)
It was to investigate the mechanism of Maspin gene methylation induced by specific shRNA primer sequences in the proliferation of oral squamous cell carcinoma (OSCC) cells. Human OSCC HN13 cell line was selected as the study object, and the corresponding specific shRNA primer sequences were designed to construct Maspin-shRNA recombinant adenovirus using human Maspin nucleotide sequences as the target gene, and it was transfected into HN13 cells. The growth curve, Maspin expression level, migration and invasion ability, and proliferation activity of the transfected cells were analyzed. The results showed that the growth efficiency of transfected cells was significantly improved, and the OD value at 450 nm of cells in the specific sequence group (SSG) was greater than that of cells in the non-specific sequence group (nSSG). Maspin methylation was higher in the SSG than in the nSSG (P < 0.05). The number of cell migration and invasion in the SSG were higher than those in the nSSG (P < 0.05). The proliferation activity of cells in the SSG was higher than that of cells in the nSSG (P < 0.05). It showed that specific shRNA sequences induced Maspin gene methylation to inhibit Maspin expression, thereby participating in the migration and invasion motility of oral squamous carcinoma cells and improving proliferative activity.